Middle managers, personnel turnover and performance: A long-term field experiment in a retail chain - Guido Friebel; Matthias Heinz; Nick Zubanov (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2020)
In an RCT, a large retail chain's CEO sets new goals for the managers of the treated stores by asking them 'to do what they can' to reduce the employee quit rate. The treatment decreases the quit rate by a fifth to a quarter, lasting nine months before petering out, but reappearing after a reminder. There is no treatment effect on sales. Further analysis reveals that treated store managers spend more time on HR and less on customer service. Our findings show that middle managers are instrumental in reducing personnel turnover, but they face a tradeoff between investing in different activities in a multitasking environment with limited resources. The treatment does produce efficiency gains. However, these occur only at the firm level.
Keywords: L2; M1; M12; M5; 330; organizations; randomized controlled trial (RCT); insider econometrics; goal-setting; communication; HR; personnel turnover and firm performance